Re-thinking Cardiac Rehabilitation: A Foucauldian Discourse Analysis - Satija, Kritika (Auckland University of Technology, 2020)
Cardiac rehabilitation (CR) is a multi-disciplinary programme offered to patients who have had a cardiac event. In New Zealand, CR programmes are funded by the district health boards and are supported by primary healthcare organisations. Three phases of CR aim to provide education, medication prescription, exercise, and self-management strategies to patients and their families/whanau. The current international guidelines for cardiac and pulmonary rehabilitation programmes involve a significant exercise component that was historically prescribed by physiotherapists (PT’s). One of the key interventions used by the PT’s is therapeutic exercise. However, recently clinical exercise physiologists (CEP's) have started sharing phase two CR and pulmonary rehabilitation practice in New Zealand. There has been an increase in CEP numbers globally, and their business is also exercise-based rehabilitation. CEP’s and PT’s have begun to share the cardiac rehabilitation space in New Zealand. This poses a professional threat to an established profession of PT’s that have been practicing globally for over a century and have established themselves as one of the largest allied health professions. Therefore, sharing of CR space and challenging the PT practice in NZ have resulted in PT’s trying to protect their professional identity and territory. This thesis explores professional boundary tensions and power relationships between healthcare professionals using Foucauldian discourse analysis to better understand how knowledge and power shape physiotherapy practice. In this thesis, I will focus on how PT’s and CEP’s compete for control of phase two CR in Aotearoa/New Zealand. This thesis uses Foucault’s ideas on discipline, governmentality, power, knowledge, truth, and discourse to explore how the practice and boundaries of CEP’s and PT’s are evolving. The thesis addresses two crucial discourses that have shaped PT’s involvement as a profession and their participation in CR. These include normalisation and biomedicine. This thesis also explores the history of CR practice, its discursive formations, the impact of power relations, and boundary tensions and how it shapes the future of PT practice in the society and healthcare system. The thesis also aims to present the current construction of CR practice, what made it possible, and how to do, speak, and think about CR. My findings in the thesis support that although CEP’s are practicing private CR outside government-funded rehabilitation and are posing a threat to physiotherapy practice. CEP’s are not necessarily taking over CR in NZ and professionals tensions such as these have been noted in the past. Although these are small shifts in phase two CR, they have resulted in PT’s reaction to protecting their professional boundaries in NZ. Viewing and analysing professional boundary tensions in CR can help explore the future possibilities of phase two CR in NZ. Lastly, this thesis will also be significant in contributing to the sociology of professions and how the healthcare professions are evolving in the 21st century.
Keywords: Foucault; Cardiac rehabilitation; Physiotherapy; Power; Hierarchy; Clinical exercise physiology; Knowledge; Professional relationships